Thermal behavior of Bose-Einstein condensates of polar molecules - J. Sánchez-Baena; G. Pascual; R. Bombín; F. Mazzanti; J. Boronat (Physical Review Research)
We use the finite-temperature extended Gross-Pitaevskii equation (TeGPE) to study a condensate of dipolar NaCs molecules under the conditions of the recent breakthrough experiment [Bigagli et al., Nature 631, 289 (2024)0028-083610.1038/s41586-024-07492-z]. We report the condensate fraction of the system and its density profile after a time-of-flight expansion for the coldest experimental case, finding excellent agreement with the experimental measurements. We also report the peak density of the ground state and establish a comparison with the experimental estimates. Our results, derived from the TeGPE formalism, successfully describe the Bose-Einstein condensation of polar molecules at finite temperature.